(untitled) (IPS Journal of Public Health, 2023)
Environmental stressors such as pollution are major sources of heavy metal toxicity in humans. Biomonitoring studies are necessary for quantifying the body burden of these metals (As, Cd, Cr, Pb, Hg) of toxicological concern and their health effects especially for communities consistently exposed to crude oil pollution. This study investigated the level of heavy metals in the blood plasma of under-five children living in crude oil-polluted and non-crude oil-polluted environments in the Niger Delta, Nigeria. This cross-sectional study was conducted in 3 crude oil polluted communities in Gokana, Rivers State (B. Derek, K. Dere, Bomu) and 3 non-crude oil exploration communities in Ideato North LGA of Imo State (Umukegwu, Umuezeaga, Owerre-Akokwa) assigned as control; both States are in Niger Delta region of Nigeria. Ethical approval was obtained from the University of Port Harcourt Ethical Committee. A total of 78 children were recruited from Gokana (male =17, female= 22) and Ideato (Male=15, female=24) using multi-clustered sampling method. Standard methods of heavy metal analysis using atomic absorption spectrophotometer were used to analyze the samples. From the results, the concentration of Cr and Cd in the blood plasma of Gokana male was 2.81mg/kg and 3.19mg/kg while Ideato male was 0.497mg/kg of Cr and Cd was not detected. Gokana female was 1.22mg/kg for Cr and 0.92mg/kg for Cd. It was concluded that under-5 children living in crude oil-polluted communities of the Niger Delta region of Nigeria have high positive levels of heavy metals (Cr, Cd and AS). Health effect of the exposures is advised considering the sensitivity of the study population.